EVALUASI KEBIJAKAN PEMERINTAH DAERAH DALAM PELAKSANAAN PROGRAM SMART CITY KOTA MADIUN - Lely Rizki Handayani; Yusuf Adam Hilman; Bambang Widiyahseno; Bambang Triono (P3M STISIPOL Dharma Wacana Metro, 2022)
Madiun City as a Smart City is a city development concept by applying and implementing technology in an innovative, effective and efficient manner by connecting physical, economic and social infrastructure in an area so as to improve services and realize a better quality of life. Smartcity is a city area that has integrated information and communication technology in daily governance with the aim of realizing efficiency, improving public services, and increasing the comfort and welfare of its citizens. The purpose of this study is to examine and analyze the evaluation of the implementation of Madiun City government policies in the implementation of smart governance, smartbranding, smarteconomy, smartliving, smartsociety and smartenvironment programs on the smartcity concept.This study uses a descriptive qualitative method approach. Qualitative research is research that produces descriptive data in the form of written or spoken words from the people observed. The results of the research are the implementation of development programs and software development to support the Smart City program strategy in all aspects of the dimensions, 80% of which have been completed in 2021 from the target until 2024 and 20% are targeted to be fully active in 2022. The results of the implementation of the Smart program City DI Madiun City in each dimension obtained from the results of the review for 2021 it is stated that the Smart Governance dimension of the governance policy program and all applications implemented are declared active, the Smart Branding dimension is stated to have run well according to the targets and targets, namely focus In the development of business systems in the field of tourism and creative industries related to tourism, the Smart Economy dimension states the supporting software for the smart city program, which functions and has economic development targets that focus on improving the quality and quantity of business in business. In terms of Creative Economy and Agriculture, for the Smart Living dimension, it is stated that all OPD and work units within the Madiun City Government have and are actively running public service applications in order to realize development strategies and targets. In the Smart Society dimension, it is stated that it has created a socio-technical ecosystem of a humanist and dynamic society, both physical and virtual for the creation of a productive, communicative, and interactive society with high digital literacy. The software facilities supporting the Smart Society dimension have been carried out well in terms of operations and performance and in the Smart Environment dimension it is stated that they have been able to realize good, integrated, and independent environmental governance (Madiun Health and Comfort City) through the land resource protection governance system. , water, and air and integrate it with reporting and monitoring technology for soil, water, and air pollution.